If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-(y2-2)=y2-5-y2
We move all terms to the left:
-(y2-2)-(y2-5-y2)=0
We add all the numbers together, and all the variables
-(+y^2-2)-(-5)=0
We add all the numbers together, and all the variables
-(+y^2-2)+5=0
We get rid of parentheses
-y^2+2+5=0
We add all the numbers together, and all the variables
-1y^2+7=0
a = -1; b = 0; c = +7;
Δ = b2-4ac
Δ = 02-4·(-1)·7
Δ = 28
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$y_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$y_{2}=\frac{-b+\sqrt{\Delta}}{2a}$
The end solution:
$\sqrt{\Delta}=\sqrt{28}=\sqrt{4*7}=\sqrt{4}*\sqrt{7}=2\sqrt{7}$$y_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(0)-2\sqrt{7}}{2*-1}=\frac{0-2\sqrt{7}}{-2} =-\frac{2\sqrt{7}}{-2} =-\frac{\sqrt{7}}{-1} $$y_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(0)+2\sqrt{7}}{2*-1}=\frac{0+2\sqrt{7}}{-2} =\frac{2\sqrt{7}}{-2} =\frac{\sqrt{7}}{-1} $
| (2m-4)^2-4(2m-4)+3=0 | | 8^x=16 | | 5x+1-3x=7-(-2x-9) | | 10x-12=12-10x | | 4,3m-3.36=5.7m | | 216^x+1=16 | | 27-3m=8m-50 | | (3x-2)/4=4 | | 4x(2x+5)(x-6)=0 | | x+3(1+2x)=17 | | 5x-19=-4 | | -64=-4x-12 | | m+7=3+m+14 | | X-72x=478 | | 2/(x-3)+(1/4)=2 | | (2x-5)*2x-3/2=0 | | 1/2b+9/7=7/4 | | 7x9=(7x10)-(7x | | x/2-8=110 | | 3+10x=-67 | | 3(7-2x)=14(-1)-8(x-1) | | (2x+41)+127=180 | | 7x+32=9x-16 | | 3(x-2)+14=-25 | | (3x+9)=(4x-8) | | 15/(-6x)=-4 | | 3x-6=2x+5(3x-2) | | 6k-(7+k)=-(5k+7) | | 1/18w-1/36+1/3w=1/3+w | | X+3=2x-6=x=36 | | 4(6r+3)+2(r=2) | | (2x^2)-12x+1=-11 |